Innovative utilization of herbal residues: Exploring the diversity of mechanisms beneficial to regulate anaerobic fermentation of alfalfa. (September 2022) - Li, Xiaomei; Chen, Fei; Wang, Xuekai; Xiong, Yi; Liu, Zhenyu; Lin, Yanli; Ni, Kuikui; Yang, Fuyu
Graphical abstract: Highlights: First to show the diverse effect of herbal residues on fermentation quality. Herbal residues addition significantly decreased NH3 -N content. Adding herbal residues changed fermentation quality by altering microbiota. Carbohydrate metabolism was enhanced with herbal residues addition. Herbal residues provided new insights for improving anaerobic fermentation. Abstract: In order to increase the utilization of herbal residues, realize efficient utilization of resources, the bacterial community and anaerobic fermentation characteristics of alfalfa ensiling treated with 36 kinds of herbal residues were studied. All the herbal residues improved the anaerobic fermentation quality in different degrees, indicated by lower pH, NH3 -N and butyric acid concentrations. However, the contents of lactic and acetic acids varied widely in silage with different herbal residues. Pearson's correlation analysis showed that the improved fermentation quality was closely associated with the variation of lactic acid bacteria community. Consequently, the herbal residues could improve anaerobic fermentation quality by stimulating desirable Lactobacillus species and inhibiting undesirable microbes. This study provides new insights for efficient utilization of herbal residues.